Identification and validation of HOXB3 hypomethylation as a novel prognostically epigenetic biomarker in acute myeloid leukemia - Zhang, Ting-juan; Chang, Ran; Xie, Fei; Xu, Zi-jun; Chu, Ming-qiang; Wu, Xiao-chi; Qian, Jun; Zhou, Jing-dong (Frontiers in Immunology, 2026)
BackgroundAberrant expression of Homeobox (HOX) genes has been observed in acute myeloid leukemia (AML), but their epigenetic regulatory mechanisms remain largely elusive. Previously, we identified HOXA9 hypomethylation, among HOXA family genes as an epigenetic biomarker for predicting clinical outcomes and guiding treatment choices in AML. Herein, we further investigated the methylation of HOXB family members in AML and determined its clinical implications.MethodsWe first systematically analyzed the association of HOXB methylation with expression and clinical outcomes in AML from The Cancer Genome Atlas (TCGA) database. Next, the candidate prognosis-related gene HOXB3 was selected for clinical relevance analysis and further verified in another independent cohort from our hospital.ResultsHypomethylation of HOXB3, which was negatively associated with its expression, was correlated with adverse prognosis among HOXB family genes in AML from TCGA datasets. Clinically, AML patients with HOXB3 hypomethylation had unique clinical subtypes and cytogenetic/molecular patterns, including FAB-M5, normal karyotype, cytogenetic/molecular-intermediate risks, and mutations in FLT3-ITD, NPM1 and DNMT3A. Despite these associations, HOXB3 hypomethylation was an independent prognostic biomarker for AML. Bioinformatics analysis demonstrated the association of HOXB3 hypomethylation with several leukemia-related genes (HOXB family genes, miR-10, miR-196a, miR-1, miR-193b and miR-379) in AML. Subsequently, we further validated aberrant HOXB3 hypomethylation and its epigenetic regulatory role in AML.ConclusionsHOXB3 hypomethylation, which is associated with HOXB3 overexpression, is a frequent event in AML. AML with HOXB3 hypomethylation usually has unique genetic patterns such as a normal karyotype, cytogenetic/molecular-intermediate risk, and mutations in FLT3-ITD, NPM1 and DNMT3A. Despite these associations, HOXB3 hypomethylation may serve as an independent prognostic biomarker for AML.